Frameworks for system integration by considering quality and cost in academic performance - Sri Nur Areena, Mohd Zaini; Mohd Yazid, Abu; Nurul Haziyani, Aris; Nur Najmiyah, Jaafar; Ahmad Shahrizan, Abdul Ghani; Emelia Sari, .; Faizir, Ramlie; Wan Zuki Azman, Wan Muhamad; Nolia, Harudin (Islamic Azad University Qazvin Branch, 2025)
In modern society, system integration, which enables multiple subsystems to function as one, is emerging in various fields such as industry, commerce, and infrastructure. Currently, the annual achievement assessment report, which combines both the annual work target (AWT) and a Likert scale assessment, is used to evaluate academicians’ performance. However, this assessment involves human judgment, which is often considered unfair. The current system framework primarily focuses on quality elements, making it insufficient for a comprehensive evaluation. Therefore, a system integration framework that relies solely on quality elements is inadequate. This study proposes four integration frameworks that consider both quality and cost: conventional activity-based costing (ABC) integration, conventional time-driven activity-based costing (TDABC) integration, Mahalanobis-Taguchi system (MTS)-ABC integration, and MTS-TDABC integration. To implement system integration, 53 parameters from the quality element are mapped to 35 sub-activities from the costing model. The second objective of this study is to validate the effectiveness of these system integrations using data from a sample of grade DS51/52 academicians. Following the calculations, the total used cost for each integration model is determined and compared. Among them, the MTS-TDABC integration is identified as the ideal model, as its used cost of MYR 69,521 is the closest to the actual supplied resource cost of MYR 70,260. This study contributes to the evaluation of academicians’ performance by offering a new perspective that integrates significant parameters with the corresponding sub-activities, leading to a more comprehensive and fair assessment system.